The diagnosis and clinical management of the catastrophic antiphospholipid syndrome: A comprehensive review. (August 2018) - Cervera, Ricard; Rodríguez-Pintó, Ignasi; Espinosa, Gerard
Abstract: The catastrophic antiphospholipid syndrome (CAPS) is a life-threating variant of the antiphospholipid syndrome characterized by the development of multiple thrombosis in a short period of time, usually ending up in the failure of function of several vital organs. Most CAPS episodes are related to a prothrombotic situation or precipitating factor such as infections, surgical procedures or malignant diseases. In patients with CAPS, the development of multiple thrombosis leads to an important cytokine release that worsens the already critical patient's situation. The disease usually involves the kidneys, the lungs and the heart, although any organ system can be affected. Although occasionally the disease affects large vessels, in the majority of cases it affects small vessels, leading to a disseminated microangiopathic syndrome resembling thrombotic thrombocytopenic purpura. Treatment is based on the administration of anticoagulants, corticosteroids, plasma exchange and/or intravenous immunoglobulins. Cyclophosphamide is recommended in those CAPS cases associated to systemic lupus erythematosus. Additionally, rituximab and eculizumab have been used in refractory cases. Mortality is still around 30% despite current treatment. Highlights: CAPS is characterized by the development of multiple thrombosis in a short period of time, mainly affecting small vessels. Most CAPS episodes are related to a precipitating factor such as infections, surgical procedures or malignant diseases. The disease usually involves the kidneys, the lungs and the heart, although any organ system can be affected. Treatment is based on the administration of anticoagulants, corticosteroids, plasma exchange and/or intravenous immunoglobulins. Rituximab and eculizumab have also been used in refractory cases. However, mortality is still around 30% despite treatment.